Transnational Terrorism and State Responses: A Comparative Study in Pakistan - Bhutto, Benazir (Journal of International Relations, 2025)
Purpose: The aim of the study was to analyze the transnational terrorism and state responses: a comparative study in Pakistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Pakistan’s battle against transnational terrorism is shaped by various external and internal factors, notably the spillover of extremist networks from neighboring regions, porous borders, and long-standing socio-political tensions. In response, the state has employed a mix of military operations, counterterrorism legislation, and intelligence-sharing initiatives, supplemented by attempts at social and economic reforms. Comparative analyses show that while Pakistan’s strategy has disrupted numerous terror networks, persistent challenges include inconsistent implementation of policies, limited regional cooperation, and the need for a more comprehensive approach that addresses both security and underlying socioeconomic grievances. Unique Contribution to Theory, Practice and Policy: Realist theory, liberal institutionalism & constructivism may be used to anchor future studies on transnational terrorism and state responses: a comparative study in Pakistan. States should adopt a holistic approach to counterterrorism that integrates military, diplomatic, and economic strategies. Policymakers must develop balanced frameworks that incorporate military actions alongside diplomatic engagement, development aid, and conflict resolution initiatives.